Sequence Typing Confirms that Campylobacter jejuni Strains Associated with Guillain-Barré and Miller-Fisher Syndromes Are of Diverse Genetic Lineage, Serotype, and Flagella Type - Dingle, K. E. (American Society for Microbiology, 2001)
Guillain-Barré syndrome (GBS) and Miller-Fisher syndrome (MFS) are correlated with prior infection by Campylobacter jejuni in up to 40% of cases. Nucleotide sequence-based typing of 25 C. jejuni isolates associated with neuropathy permitted robust comparisons with equivalent data from approximately 800 C. jejuni isolates not associated with neuropathy. A total of 13 genetic lineages and 20 flaA short variable region nucleotide sequences were present among the 25 isolates. A minority of isolates (4 of 25) had the flaA short variable region nucleotide sequences that were previously proposed as a marker for GBS-associated isolates. These 4 isolates probably represented the Penner serotype 19 lineage, which has been proposed to have an association with GBS.